A Novel Approach of Perturb and Observe Technique Adapted to Rapid Change of Environmental Conditions and Load. Issue 4 (6th August 2020) - Belkaid, Abdelhakim; Colak, Ilhami; Kayisli, Korhan
Abstract: The basic P&O technique fails to track the MPP when a rapid change in luminosity and/or temperature has occurred because it cannot distinguish between disturbance of PV voltage and rapid change in environmental conditions. This study presents drawbacks of the basic algorithm and proposes a new variant of P&O with three incremental steps to differentiate the two states mentioned above, thus avoiding divergences in the MPPT path. The suggested MPPT command consists of a modified P&O algorithm applied to a boost converter to overcome poor transient responses and thus optimize the efficiency of the entire PV system. The proposed tracker is built using a 60 W module and its performance is verified by simulations with MATLAB tools considering quick change in the solar irradiance, temperature and load. The test results demonstrate the feasibility and improved performance of the system. The modified P&O technique effectively tracks the MPP in various work situations and capable of increasing energy transfer efficiency by nearly 5%.